2017
DOI: 10.1002/cyto.b.21491
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter Single Cell Profiling of Airway Inflammatory Cells

Abstract: Airway diseases affect over 7% of the U.S. population and millions of patients worldwide. Asthmatic patients have wide variation in clinical severity with different clinical and physiologic manifestations of disease that may be driven by distinct biologic mechanisms. Further, the immunologic underpinnings of this complex trait disease are heterogeneous and treatment success depends on defining subgroups of asthmatics. Due to the limited availability and number of cells from the lung, the active site, in-depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Nine subjects with a confirmed CF diagnosis from the Yale Adult CF Program provided sputum samples. We also recruited five HC to undergo sputum induction according to previous protocols (22). Study subjects were closely age-matched, with a higher inclusion of female subjects in the CF group (67% CF, n=6, 40% HC, n=2).…”
Section: Disease-specific Cell Distributions Of Cf Airway Inflammatormentioning
confidence: 99%
“…Nine subjects with a confirmed CF diagnosis from the Yale Adult CF Program provided sputum samples. We also recruited five HC to undergo sputum induction according to previous protocols (22). Study subjects were closely age-matched, with a higher inclusion of female subjects in the CF group (67% CF, n=6, 40% HC, n=2).…”
Section: Disease-specific Cell Distributions Of Cf Airway Inflammatormentioning
confidence: 99%
“…One of the most prominent application of HDcyto technology is the investigation of human pathologies, as it allows a deep understanding of inter‐cellular perturbations and the identification of disease‐specific signatures that may serve as diagnostic biomarkers or, eventually, therapeutic targets. HDcyto has already proved to be a powerful platform for the investigation of idiopathic syndromes and pathologies with incomplete understanding of disease‐driving mechanisms .…”
Section: Identification Of Molecular Signatures and Disease‐associatementioning
confidence: 99%
“…Distinct monocyte/macrophage and granulocyte cell populations distinguished asthmatic patients from cystic fibrosis patients and healthy controls. The method proved to be especially useful for dissecting a heterogeneous condition like asthma into groups with different immunological characteristics which, might reflect differences in disease pathophysiologies and could help to make individualized therapeutic decisions in the future .…”
Section: Identification Of Molecular Signatures and Disease‐associatementioning
confidence: 99%
“…We highlight six studies that illustrate recent progress. The manuscripts by Yao et al , Corneau et al , and Strauss‐Albee et al emphasize the utility of mass cytometry for identifying cell subsets that capture patient‐specific disease attributes in the fields of pulmonology, neonatology, and virology. The studies by Abraham et al and Vendrame et al apply visualization and statistical tools in novel combinations to interpret high‐dimensional data, while the manuscript by Leelatian et al describes a standardized protocol to derive isolated cancer cells from solid tissue for analysis by mass cytometry.…”
mentioning
confidence: 99%
“…Yao et al demonstrate the utility of multiparameter profiling of airway inflammatory cells in patients with cystic fibrosis (CF) to better understand the complex interactions between an individual's immune state and disease severity. Using a novel assay for the mass cytometry analysis of airway inflammatory cells, the authors identified significant differences in the frequency of immune cell subsets in sputum collected from patients with CF, patients with asthma, and healthy controls.…”
mentioning
confidence: 99%